EVALUASI HASIL BELAJAR DALAM IMPLEMENTASI KURIKULUM BERBASIS KOMPETENSI DI SEKOLAH MENENGAH KEJURUAN - Edy Purnomo & Sudji Munadi (LPMPP Universitas Negeri Yogyakarta, 2005)
AbstractThe effort of preparation manpower quality can be done not only by vocational education but also by other institutions. The output quality of vocational education has been valued that it is not enough optimum in the some qualification of business and industrial sectors. So that, the kind of this school has been improving continuously its performance to increase output quality.Many kinds of the programs have been applicated likes link and match education system, life skill programe and nowadays the Competency Based Curriculum is being actively socialized. By implementing this curriculum will be expected that students learning outcome or the output of educational processcan support the competencies criterion which had been formulated.Being able to evaluate the competencies as students learning outcome is needed the acccurate and proper of evaluation system. In this case, the Basic Classroom Evaluation which is one of the components of Competency Based Curriculum must be payed attention. By having knowledge the concept of criterion reference evaluation it is expected that the teachers can measure and evaluate students competencies according to a real condition of them.Key words: competencies, measurement, evaluation and standard